CONTROLLING THE BORROWER POPULATION OF P2P LENDING MODELS - Gunadi, Audri Utami; Handayani, Dewi (Journal of the Indonesian Mathematical Society, 2024)
P2P lending, commonly called online lending, is a service provider institution that provides borrowing and lending services in rupiah currency through an electronic system. The growth of P2P lending has increased rapidly since the pandemic of COVID-19 and led to an increase in the number of borrowers. Meanwhile, crime has also increased as many people can’t repay their loans. The chain of P2P lending must be controlled to suppress the growth of the population of people with online loans. This study constructs two P2P lending models by modifying the Kermack-McKendrick Epidemic Model. The population is divided into three sub populations: potential individuals, borrowers, and payers. Optimal control is used to suppress the population growth of borrower individuals through socialization with potential individuals or people with work potential and providing payment assistance for borrowers. This study constructs several optimal control scenarios for the two P2P lending models. From the comparison of optimal control scenarios, the optimal control recommendations that can suppress the population growth of borrower is to provide socialization to people with work potential and payment assistance for the borrower population.